ANXA2 remodels the microstructures of caco2 cells - Xing, R.; He, H.; He, Y.; Feng, Y.; Zhang, C.; Wu, H.; Sun, M.; Yu, X.; Liu, Y.; Song, X.; Wang, X.; Chen, Y.; et al. (Cellular and Molecular Biology, 2013)
ANXA2 was reported as a multiple tumors relevant gene expressed excessively in many tumor tissue types, especially in the cancers from digestion system, and its aberrant expression enhances the malignant properties of cancer cells. We suppose that the microstructure heterogeneity is important to maintain the malignancy of cancer cells, and excessive ANXA2 expression enhance the malignancy by remodeling the microstructures of cancer cells. To validate the proposal, the ANXA2-/-caco2 cell line was generated and the changes of the microstructures in the ANXA2 deleted and wild type caco2 cells were observed under fluorescence microscope, laser scanning confocal microscope and electron microscope. We found that ANXA2 deletion induced the pseudopodia shorted and spared, non-stained areas increased, mitochondria decreased, and the expression and polymerization of F-actin and Î²-tubulin changed. By the findings above, it is firstly reported in this paper that the ANXA2 excessive expression induces the significant changes of the microstructures in cancer cells. Combining our previous data together, our results indicate that ANXA2 excessive expression enhances the malignancy of cancers partially by remodeling the cell microstructures.